CACNA1A-Linked Hemiplegic Migraine in GLUT 1 Deficiency Syndrome: A Case Report - Scoppola, Chiara; Magli, Giorgio; Conti, Marta; Fadda, Maria; Luzzu, Giovanni M.; Simula, Delia M.; Carta, Alessandra; Sotgiu, Stefano; Casellato, Susanna (Frontiers in Neurology, 2021)
Background: Glucose-transporter-1 deficiency syndrome (GLUT1-DS), due to SLC2A1 gene mutation, is characterized by early-onset seizures, which are often drug-resistant, developmental delay, and hypotonia. Hemiplegic migraine (HM) is a rare form of migraine, defined by headache associated with transient hemiplegia, and can be caused by mutations in either CACNA1A, ATP1A2, or SCN1A. Paroxysmal movements, other transient neurological disorders, or hemiplegic events can occur in GLUT1-DS patients with a mild phenotype. Case: We report on a girl with GLUT1-DS, due to SLC2A1 mutation, with a mild phenotype. In early childhood, she developed epilepsy and mild cognitive impairment, balance disorders, and clumsiness. At the age of 9, the patient reported a first hemiplegic episode, which regressed spontaneously. Over the next 3 years, two similar episodes occurred, accompanied by headache. Therefore, in the hypothesis of HM, genetic testing was performed and CACNA1A mutation was identified. The treatment with Lamotrigine avoided the recurrence of HM episodes. Discussion: To our knowledge, among the several cases of GLUT1-DS with HM symptoms described in the literature, genetic testing was only performed in two of them, which eventually proved to be negative. In all other cases, no other genes except for SLC2A1 were examined. Consequently, our patient would be the first description of GLUT1-DS with HM due to CACNA1A mutation. We would emphasize the importance of performing specific genetic testing in patients with GLUT1-DS with symptoms evocative of HM, which may allow clinicians to use specific pharmacotherapy.